BEDA LUARAN FUNGSI SENSORIMOTOR PASIEN DENGAN DAN TANPA FATIGUE PASCASTROKE ISKEMIK - Maria Putri Utami,* Hexanto Muhartomo,* Maria Immaculata Widisastuti* (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION POSTSTROKE FATIGUE IS A BURDEN IN IMPROVING NEUROLOGICAL DEFICITS REHABILITATION QUALITY OF LIFE AND CAPACITY AT WORK THUS THE CONSEQUENCES OF POSTSTROKE FATIGUE SHOULD BE DEALT SERIOUSLY CONSIDERING THIS IS A PROBLEM FOR THE PATIENTS AND DIFFICULT TO DEAL WITH